Gene Expression of Protein Tyrosine Phosphatase 1B and Endoplasmic Reticulum Stress During Septic Shock - Clavier, Thomas; Grangé, Steven; Pressat-Laffouilhere, Thibaut; Besnier, Emmanuel; Renet, Sylvanie; Fraineau, Sylvain; Thiebaut, Pierre-Alain; Richard, Vincent; Veber, Benoit; Tamion, Fabienne (Frontiers in Medicine, 2019)
Introduction: Protein Tyrosine Phosphatase 1B (PTP1B) and endoplasmic reticulum stress (ERS) are involved in the septic inflammatory response. Their inhibition is associated with improved survival in murine models of sepsis. The objective was to describe PTP1B and ERS expression during septic shock in human. Material and Methods: Prospective study including patients admitted to intensive care unit (ICU) for septic shock. Blood samples were collected on days 1 (D1), 3 and 5 (D5). Quantitative PCR (performed from whole blood) evaluated the expression of genes coding for PTP1B (PTPN1) and key elements of ERS (GRP78, ATF6, CHOP) or for endothelial dysfunction-related markers (ICAM1 and ET1). We analyzed gene variation between D5 and D1, collected glycemic parameters, insulin resistance and organ failure evaluated by Sequential Organ Failure Assessment (SOFA) score. Results: We included 44 patients with a mean SAPS II 50 ± 16 and a mortality rate of 13.6%. Between D1 and D5, there was a significant decrease of PTPN1 (p<0.001) and ATF6 (p<0.001) expressions. Their variations of expression were correlated with SOFA variation (PTPN1, r=0.35, CI95%[0.05;0.54], p=0.03 and ATF6, r=0.45 CI95%[0.20;0.65], p<0.001).We did not find any correlation between PTPN1 expression and insulin resistance or glycemic parameters. Between D1 and D5, ATF6 and PTPN1 expressions were correlated with that of ET1. Conclusions: Our study has evaluated for the first time the expression of PTP1B and ERS in patients with septic shock, revealing that gene expression variation of PTPN1 and ATF6 are partly correlated with the evolution of septic organ failure and with endothelial dysfunction markers expression.